2011
DOI: 10.5540/tema.2011.012.03.0195
|View full text |Cite
|
Sign up to set email alerts
|

Usando o ATSP na Modelagem do Problema Integrado de Produção de Bebidas

Abstract: Resumo. Neste trabalho, propomos um modelo integrado de dimensionamento de lotes e programação da produção monomáquina para uma fábrica de refrigerantes de pequeno porte. As decisões de dimensionamento foram baseadas em um modelo encontrado na literatura e as decisões de sequenciamento foram modeladas utilizando restrições do problema do caixeiro viajante assimétrico. Para a validação do modelo proposto foram feitos testes computacionais com exemplares gerados aleatoriamente, e também exemplares baseados em da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The complete description of the P1S1MTS model is given by expressions (1)-(15). More details on the P1S1MTS model can be obtained from Defalque et al (2011). Other formulations of the soft drink production process can be found in Toledo et al (2007), Ferreira et al (2009 and2010).…”
Section: Stage II (Bottling) -Schedulingmentioning
confidence: 99%
“…The complete description of the P1S1MTS model is given by expressions (1)-(15). More details on the P1S1MTS model can be obtained from Defalque et al (2011). Other formulations of the soft drink production process can be found in Toledo et al (2007), Ferreira et al (2009 and2010).…”
Section: Stage II (Bottling) -Schedulingmentioning
confidence: 99%
“…Esteé o caso das indústrias de bebidas não alcoólicas, cujas características fazem com que encontrar planos de produção factíveis seja altamente complexo [1,2,3]. Este processo, composto principalmente de dois estágios de produção e será descrito na Seção 2.…”
Section: Introductionunclassified
“…Regarding the problem, the production bottleneck alternates between the liquid preparation stage and the bottling one, therefore synchronization of the production between these stages is required. Other related studies appear in Ferreira et al (2010Ferreira et al ( , 2012 and Defalque et al (2011). Leite (2008) is the only study found in the literature review that deals with the production problem of a line of fruit beverages.…”
Section: Introductionmentioning
confidence: 99%